4
$\begingroup$

On a real analysis worksheet i was given, the following question is posited.

Let $f_n$ be the Fibonacci sequence defined by $f_1=1, f_2=1$ and for $n>2, f_{n+1}=f_n+f_{n-1}$. Show that for all $n>2,$ $$f_{n+1}f_{n-1}=(-1)^nf_n^2$$

I can't help but think that this is a typo. All Fibonacci numbers are positive, and a basic substitution of $n=3$ would give

$$f_{4}f_2=3\neq-4=(-1)^3f_3^2$$

If it is a typo, does anyone know the actual identity that is being questioned here?

$\endgroup$
  • 2
    $\begingroup$ It should be $F_{n+1}F_{n-1}-F_n^2=(-1)^n$. $\endgroup$ – carmichael561 Nov 12 '16 at 19:45
  • $\begingroup$ Thank you. I knew something was wrong. $\endgroup$ – Iceman Nov 12 '16 at 19:46
4
$\begingroup$

It's supposed to be $f_{n + 1} f_{n - 1} = f_n^2 + (-1)^n$, which is called Cassini's identity.

$\endgroup$
2
$\begingroup$

A simple proof for the Cassini's identity is in the following form . Consider the following matrix that is well-know to $Q_p$ matrix $$ Q_2=\left[ \begin{array}{cc} 0 & 1 \\ 1 & 1 \end{array} \right] \, . $$ with the induction on $n$, we can prove that the $n$th power of matrix $Q_2$, is in the following form $$ Q_2^n= \left[ \begin{array}{cc} F_{n-1} & F_{n} \\ F_{n} & F_{n+1} \end{array} \right]\, . $$ In addition, the determinant of matrix $Q_2$ is $(-1)$ and because of this we conclude that $$ det(Q_2^{n})={(-1)}^{n}\, . $$ the above relation, results that $$ det( \left[ \begin{array}{cc} F_{n-1} & F_{n} \\ F_{n} & F_{n+1} \end{array} \right] )={(-1)}^{n} \Longrightarrow F_{n-1}F_{n+1}-F_{n}^2={(-1)}^{n}\, . $$ Another proof for the Cassini's identity is as follows \begin{eqnarray} F_{n+1}F_{n-1}-F_{n}^2&=&(F_{n-1}+F_{n})F_{n-1}-F_{n}^2 \\ \\ &=& F^2_{n-1}+F_n(F_{n-1}-F_n) \\ \\ &=&F^2_{n-1}-F_nF_{n-2} \\ \\ &=&-(F_nF_{n-2}-F^2_{n-1}) \end{eqnarray} With repetition the mentioned process, we get

\begin{eqnarray} -(F_nF_{n-2}-F^2_{n-1})&=& {(-1)}^2(F_{n-1}F_{n-3}-F^2_{n-2}) \\ \\ &=&{(-1)}^3(F_{n-2}F_{n-4}-F^2_{n-3}) \\ \\ && \vdots \\ &=& {(-1)}^n(F_{1}F_{-1}-F^2_{0}) \\ \\ &=& {(-1)}^n \end{eqnarray}

The last row is true, because of the following relation between Fibonacci numbers $$ F_{-n}={(-1)}^{n+1}F_n \, . $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.